2015
DOI: 10.1021/jacs.5b08798
|View full text |Cite
|
Sign up to set email alerts
|

Single Enzyme Experiments Reveal a Long-Lifetime Proton Leak State in a Heme-Copper Oxidase

Abstract: Heme-copper oxidases (HCOs) are key enzymes in prokaryotes and eukaryotes for energy production during aerobic respiration. They catalyze the reduction of the terminal electron acceptor, oxygen, and utilize the Gibbs free energy to transport protons across a membrane to generate a proton (ΔpH) and electrochemical gradient termed proton motive force (PMF), which provides the driving force for the adenosine triphosphate (ATP) synthesis. Excessive PMF is known to limit the turnover of HCOs, but the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 45 publications
4
58
0
Order By: Relevance
“…bo 3 was studied at single‐molecule level. The results from these studies suggested that an oxidase molecule could enter a “long‐lifetime leak state” during turnover . This is a surprising observation because a proton leak across any of the cyt.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…bo 3 was studied at single‐molecule level. The results from these studies suggested that an oxidase molecule could enter a “long‐lifetime leak state” during turnover . This is a surprising observation because a proton leak across any of the cyt.…”
Section: Introductionmentioning
confidence: 91%
“…bo 3 per liposome. While in the earlier study electrons were supplied to the cyt. bo 3 via a gold electrode, in the present study the electrons were supplied from ubiquinol (UQ 1 ) and the reducing agent dithiothreitol (DTT).…”
Section: Introductionmentioning
confidence: 99%
“…Patch clamp recording has made it possible to observe the functional dynamics of single ion channels revealing discrete on and off states, subconductance states, and other mechanistically important features that macroscopic experiments cannot probe (2). However, despite extensive structural and biochemical efforts (3), we currently lack a similar depth of understanding of transporters because they in general do not produce electrically detectable single-molecule transport signals (48). Here we monitored at the single-molecule level the functional dynamics of a eukaryotic primary active transporter, Arabidopsis thaliana H + -ATPase isoform 2 (AHA2, referred to as the proton pump), which is responsible for energizing the plasma membrane of plants and fungi (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…[9] Inspired by this finding,w e present herein as et of noncovalently associated C 60 -pphenylene oligomers,i nw hich the p-conjugation length of the oligomers in the bridges has been systematically altered. [11] From as ynthetic perspective,a symmetric p-phenylene oligomers with aldehyde and carboxylic termini are the key intermediates en route to pyrrolidino[3,4:1,2][60]fullerenes 1a-d.T hese oligomers were synthesized by Suzuki crosscoupling reactions between bromoaryl and organoborane compounds in the presence of ap alladium(II) catalyst and afluorine salt as abase and additive,which is crucial for the success of the cross-coupling reaction. On the basis of this molecular design, we determined the effects of distance and the rate at which electron-transfer processes occur,a sw ell as the molecularwire behavior of systems based on p conjugation and hydrogen bonds.T his bioinspired approach combining electron transfer through supramolecular and covalent connectivity resembles charge transport in av ariety of natural processes, such as photosynthesis [10] and cellular respiration.…”
mentioning
confidence: 99%
“…On the basis of this molecular design, we determined the effects of distance and the rate at which electron-transfer processes occur,a sw ell as the molecularwire behavior of systems based on p conjugation and hydrogen bonds.T his bioinspired approach combining electron transfer through supramolecular and covalent connectivity resembles charge transport in av ariety of natural processes, such as photosynthesis [10] and cellular respiration. [11] From as ynthetic perspective,a symmetric p-phenylene oligomers with aldehyde and carboxylic termini are the key intermediates en route to pyrrolidino[3,4:1,2][60]fullerenes 1a-d.T hese oligomers were synthesized by Suzuki crosscoupling reactions between bromoaryl and organoborane compounds in the presence of ap alladium(II) catalyst and afluorine salt as abase and additive,which is crucial for the success of the cross-coupling reaction. [12] Subsequent 1,3dipolar cycloaddition reactions were used to link the pphenylene oligomers to C 60 through apyrrolidine ring to yield 1a-d in high yields (see the Supporting Information for synthetic details).…”
mentioning
confidence: 99%